Biotechnology in Comparative Perspective - Fuchs, Gerhard;Ed (Studies in Global Competition, v. 16., 2003)
With contributions from an international array of experts, this book explains why biotechnology companies in different countries are concentrated in a small number of locations and what accounts for their success.